Hubungan perilaku pemeliharaan kesehatan gigi dan mulut terhadap karies pada anak Sekolah Dasar 1 Astina Kabupaten Buleleng, Singaraja-Bali - Putu Eka Mery Utami Putri Sari; Putu Ratna Kusumadewi Giri; Ni Wayan Arya Utami (Bali Dental Journal, 2019)
Introduction: Dental caries in children is a very important issue and a major of dental and oral diseases in Indonesia. Caries is caused by multifactorial, four main factors including Host, Substrate, Microorganisms, and Time. The most influential of the high prevalence of caries is the behaviour. Behaviour of dental and oral health care has an important role to influence the dental and oral health status. Behaviour of dental and oral health care such as toothbrushing behaviour, consumption of food, and dentist visits. The purpose of this study was describing the relationship between behaviour of dental and oral health care against caries among student of SD 1 Astina Singaraja. Method: This study was an observasional analytic study using a cross-sectional approach. Sample number were 102 students who selected by Simple Random Sampling technique. Data were collected by questionnaire and screening with sonde and mouth mirror sterile. Result: Chi square test result showed p value = 0.005 (p<0.05) at the behaviour of dental and oral health care both in def-t and DMF-T categories. Conclusion: It can be cocluded that there were relationship between behaviour of dental and oral health care against caries among student of SD 1 Astina Singaraja p=0.005 (p<0.05).